2014
DOI: 10.5812/ircmj.12464
|View full text |Cite
|
Sign up to set email alerts
|

Studying Intense Pulsed Light Method Along With Corticosteroid Injection in Treating Keloid Scars

Abstract: Background:Results of various studies suggest that the hypertrophic and keloid scars are highly prevalent in the general population and are irritating both physically and mentally.Objective:Considering the variety of existing therapies, intense pulsed light (IPL) method along with corticosteroid injection was evaluated in treating these scars.Materials and Methods:86 subjects were included in this clinical trial. Eight sessions of therapeutic intervention were done with IPL along with corticosteroid intralesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(21 reference statements)
0
7
0
Order By: Relevance
“… 87 In one clinical study, keloids were 89.1% improved, as measured by the Vancouver Scar Scale (VSS), after IPL when combined with corticosteroid injection. 88 Although IPL is not entirely free from side effects ( e.g. , incidental pain, blistering, and purpura), its prevalence is much lower than that of other interventions for HS.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“… 87 In one clinical study, keloids were 89.1% improved, as measured by the Vancouver Scar Scale (VSS), after IPL when combined with corticosteroid injection. 88 Although IPL is not entirely free from side effects ( e.g. , incidental pain, blistering, and purpura), its prevalence is much lower than that of other interventions for HS.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…Similar to our results, the literature shows that patients with keloid present an average age between 24 and 35.7 years [ 3 , 38 ] and the appearance of these lesions occurs between 11 and 40 years [ 39 ]. It has been suggested that this age group is associated with hormonal changes, surgery, trauma [ 40 ], increased exposure to lesions by perforations, such as earrings/piercings [ 41 ], and also a higher recurrence during pregnancy [ 42 ]. In our study, there was a prevalence of nonwhite, which has also been reported in the literature [ 41 , 43 ], and studies have been conducted to prove the presence of genetic factors from family heredity and the frequency in specific ethnic populations [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…91 IPL targets both hemoglobin and melanin, improving pigmentation and vasculatity. 91,92 IPL technology advantage over PDL (dye lasers) is the lower incidence of postoperative purpura; it rather increases the blood vessel temperature, leading to coagulation and destruction. 93 Pulsed dye lasers deliver a 585-nm wavelength at a shortpulse duration (450 μs), allowing a penetration depth of only 1.5 mm, while IPL enables deeper-seated vessels.…”
Section: Corticosteroid Drugsmentioning
confidence: 99%
“…41,83 Intense pulsed light Intense pulsed light emits broad light wavelengths (400-1200 nm), and it has been used to treat scars for more than 15 years. 91 Some IPL machines allow to use blocking filters in wavelengths that vary from 515 up to 755 nm to prevent emission of optical ray with shorter wavelengths. 91 IPL targets both hemoglobin and melanin, improving pigmentation and vasculatity.…”
Section: Corticosteroid Drugsmentioning
confidence: 99%